Indicadores de gestión de calidad en empresas del sector manufactura (2016)
This project presents a proposal for the creation of management indicators focused on measuring the management of companies in the manufacturing sector under the PHVA approach. The presented methodology covers four sequential stages, starting with the identification and analysis of the processes of the quality management system, from which the process map is structured as an example for the development of quality management indicators. Continuing with the identification of the critical activities in each process and the key success factors or components of the quality policies from which the objectives of the organization are developed and the indicator is designed according to the characterization sheet